Physostegia virginiana (L.) Benth - Carbone, Lucas M. (Herbario ACOR, Facultad de Ciencias Agropecuarias, Universidad Nacional de Córdoba, 2022)
Carbone, Lucas M. Herbario ACOR, Facultad de Ciencias Agropecuarias, Universidad Nacional de Córdoba.